Molecular diversity of the Planctomycetes in the human gut microbiota in France and Senegal. Issue 11 (18th April 2013) - Cayrou, Caroline; Sambe, Bissoume; Armougom, Fabrice; Raoult, Didier; Drancourt, Michel
Abstract : Until now, Planctomycetes bacteria were considered as environmental organisms. Nevertheless, some studies detected Planctomycetes DNA from human gut. We therefore explored the human gut Planctomycetes content. Planctomycetes ‐specific PCR primers were designed to amplify a 240–bp 16S rRNA gene fragment in human stool specimens from individuals in France and in Senegal and from endocarditis patients receiving antibiotics in France. PCR products were then cloned and sequenced. PCR detection revealed a significantly higher prevalence (1.8% vs 0.4%, p = 0.05) and higher diversity (62 vs 6 phylotypes, p = 0.02) of Planctomycetes 16S rRNA gene in stool specimens collected in Senegal than in France. Also, stool specimens from endocarditis patients exhibited non‐significantly higher prevalence (0.6% vs 0.4%) and the ratio of phylotypes by positive patient (3 vs 1.5) than those collected from untreated French individuals. Gemmata sp. related sequences were found in 6/12 individuals. Planctomycetes organisms are a part of the human digestive tract microbiota. Their diversity varied by environment including the geographical origin of the individual and antibiotics treatment.